2015
DOI: 10.1002/mop.29332
|View full text |Cite
|
Sign up to set email alerts
|

A novel CPW‐fed antenna with dual band‐notched charectrestics for UWB applications

Abstract: near the influential materials if the proximity effect is either an advantage or a disadvantage for an antenna system, depending on the size of an element materials, and small antenna is a small example ceramic chip antenna encapsulated in a cubic millimeters, using ESA and PSA as well. When designing a chip ceramic ESA, the dimensions of the mobile terminal device, the space for mounting the antenna, the space to be occupied by the antenna, and the antenna size [11]. FUNDAMENTAL LIMITATIONSmall antennas to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…This indicates good diversity performance is achieved by proposed antenna and good isolation between the two antennas in the MIMO systems. It can be seen that proposed antenna gives better performance in terms of gain, isolation, and ECC compares to existing ones . In the proposed design it has been observed that variation in width of slot on feeding line gives variation in notched band.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…This indicates good diversity performance is achieved by proposed antenna and good isolation between the two antennas in the MIMO systems. It can be seen that proposed antenna gives better performance in terms of gain, isolation, and ECC compares to existing ones . In the proposed design it has been observed that variation in width of slot on feeding line gives variation in notched band.…”
Section: Resultsmentioning
confidence: 82%
“…Isolation of proposed antenna is below −12 dB and correlation coefficient is less than 0.001 throughout the wideband spectrum. The gain of proposed antenna is compared with reported literature . The proposed structure can be used in any diversified wireless system where high gain, band rejection capability is an important issue.…”
Section: Introductionmentioning
confidence: 99%
“…The new generation of wireless and mobile communications systems plays an essential role in the MSA [2]. Many similar antennas have been proposed, often with dimensions too enormous for practical application [3, 4]. A large and very complex radiating patch used in [3] and in [4] a CPW fed antenna using two stepped impedance resonators are presented.…”
Section: Introductionmentioning
confidence: 99%
“…Wireless local area network (WLAN) and worldwide interoperability for microwave access (WiMAX) have been widely applied in mobile devices, such as handheld computers and intelligent phones [2]. Also many efforts in UWB antenna fields have been reported that more descriptions come in [3][4][5][6][7][8][9][10][11].…”
mentioning
confidence: 99%